Differential Responses of Liver and Hypothalamus to the Nutritional Condition During Lactation and Adult Life - Mariano, Isabela Ramos; Yamada, Laís Akemi; Soares Rabassi, Renan; Rissi Sabino, Vanessa Lara; Bataglini, Camila; Azevedo, Silvia Carla Santana Ferreira; Garcia, Rosângela Fernandes; Pedrosa, Maria Montserrat Diaz (Frontiers in Physiology, 2020)
It was previously reported that liver glucose metabolism in rats under caloric restriction differs from that of freely-fed rats. This study hypothesized that these changes 1) were related to the expression of hypothalamic neuropeptides involved in metabolic control, and 2) were not a residual effect of litter size. To those purposes, liver glucose metabolism and hypothalamic expression of the orexigenic neuropeptides NPY (neuropeptide Y) and AgRP (agouti gene-related peptide); and of the anorexigenic neuropeptides POMC (pro-opiomelanocortin) and CART (cocaine- and amphetamine-related transcripts). were investigated. Male Wistar rats from two different litter sizes (G6 and G12, with 6 or 12 pups, respectively) were subjected to free feeding (GL, ad libitum), 50% caloric restriction (GR) or caloric restriction+ad libitum refeeding (GRL) until the age of 90 days. Biometric values were lower in GR than in GL, while in GRL they were totally or partially recovered. Blood glucose variation during the pyruvate tolerance test (PTT) was small in GR. During in situ liver perfusion, total, basal and adrenaline-stimulated liver glucose outputs were high in GR, but additional glucose output in the presence of alanine was negligible. Refeeding (GRL) yielded values close to those of GL. Litter size did not consistently influence any of these variables. The expression of transcripts of the hypothalamic neuropeptides was responsive to feeding regimen, litter size and/or their interaction and differed from G6 to G12, while the metabolic changes of the liver were qualitatively equal in both GR. Therefore, the changes in glucose metabolism in the liver of rats under caloric restriction were not determined by either litter size or hypothalamic neuropeptide expression and were linked only to the prevailing feeding regimen of the adult animal.